Literature Review : Th Effect Of Giving Bean Juice On The Incidence Of Anemia And Menorrgagiain Mothers Who Use Iud - Hermawati Hamalding (Jurnal Komunitas Kesehatan Masyarakat, 2021)
The impact of menorrhagia is iron deficiency anemia. Loss of blood can lead to anemia caused by excess bleeding, surgery or problems with blood clotting. The amount of blood lost due to menstruation in women can also lead to anemia. Anemia can be prevented by consuming green bean juice. This study literature aims to determine the influence of giving green beans juice on anemia and menorrhagia in IUD users. The method used narrative descriptive method in study literature form which is done by searching literature through google scholar, PMC and portal garuda. The literature that used was published in 2010-2020 through nationally or internationally which is relevant to the topic that taken. The result obtained 5 journals with 3 books that state the influence of giving green beans juice on anemia due to menorrhagia. So it can be concluded that there is an effect of giving green bean juice on the incidence of anemia.